PENGARUH PELARUT ORGANIK DAN WAKTU PERKOLASI TERHADAP SIFAT OLEORESIN KULIT KAYU MANIS - Bambang Wiyono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
Tfl'is paper is to 1tudy the effect of organicsolvents and percolation time on oleoresinproperties of COllBia veru bark. The organic solvents used during the percolation process to extract the oleoreain consist of ethanol and acetone. Each extraction required percolation time, consecutively 2, 3, and 4 hou'f'fl. The temperature of each procea was milintained at 40° C. The experiment was conducted u1ing the factorial design, and the trend effect. of percolation time was 011Bea sed by using polynomial orthogonal analysis.The • results indicated that the eaential oil and cinnamaldehyde contents extracted with ethano,l aolvent were both significantly higher than those using acetone solvent. The polynomial orthogonal analysis revealed that the incieasing percolation time was linearly correlated with an increase in oleoresin yield and tiie essential oil contents. As for the ethanol the increaaein percolation time tent to decrease the cinnamaldehyde only. After the percolation proceBB, only the ethanol after solvent could be recovered by the redistillation proeese; •